Case report: Intranasal esketamine for severe major depressive disorder with psychotic features - Carter, Maximilian; Solsrud, Kassandra; Mischel, Nicholas (Frontiers in Psychiatry, 2022)
Introduction: About one third of patients with major depressive disorder (MDD) have treatment resistant depression (TRD). The difficulty of treating TRD especially in those with suicidal ideation and psychotic features demands treatments that are fast-acting, safe, and effective. Limited access, lack of viable options, and incomplete characterization of rapid-acting antidepressants has prevented widespread incorporation into treatment of patients with TRD. However, ketamine and its variations have shown promise of being effective treatment options for patients with TRD with psychotic features. Case Description: This 28-year-old patient with TRD with psychotic features received 14 treatments of intranasal esketamine over a three-month period. This patient initially presented with anhedonia, difficulty sleeping, suicidal thoughts, and auditory hallucinations. The Quick Inventory of Depressive Symptomology (QIDS) was used to assess depression before each session. Results: After her first two treatment sessions within a week, this patient experienced a reduction in depression from severe to moderate according to the QIDS. Over 14 sessions, she had no significant adverse effects and was stabilized to mild depression without suicidal ideations. One year after treatment, she continues to be stable. She has not had auditory hallucinations since the esketamine treatment. Conclusions: This case report provides an example of a patient with severe TRD with psychotic features that showed significant improvement after treatment with intranasal esketamine. Larger studies are indicated to further elucidate the effectiveness and safety of intranasal esketamine, so it can be more widely used for patients with TRD with psychotic features.